Effects of stocking density on growth of zebrafish (Danio rerio, Hamilton, 1822) (Bangladesh Journal of Zoology, 2017)
The effect of stocking density on growth of zebra fish was examined. Total five different stocking densities (5, 15, 25, 35 and 45 individuals per 2 liters of water) were maintained in triplicate for a period of 60 days. One month old zebrafish were randomly stocked into 15 tanks and fish were fed with commercial diet. The mean weight gain, specific growth rate and length gain for treatment 1 (5 fish/2liter) and treatment 2 (15 fish/2 liter) were significantly (p < 0.05) higher than treatment 3 (25 fish/2 liter), treatment 4 (35 fish/2 liter) and treatment 5 (45 fish/2 liter). The gender weight gain, survival rate and condition factor did not show any significant (p > 0.05) difference among treatments. The result of this study suggests that the stocking density of zebrafish could be 15 fish per 2 litre of water in a laboratory system with aeration.Bangladesh J. Zool. 44(2): 209-218, 2016